Dual wavelength continuous wave laser using a birefringent filter - Treviño-Palacios C. G.; Zapata-Nava O. J.; Mejía-Uriarte E. V.; Qureshi N.; Paz-Martínez G.; Kolokolstev O. (Journal of the European Optical Society-Rapid Publications, 2013)
We report simultaneous dual wavelength continuous laser emission with minimum cavity elements. Tunable dual wavelength emission between 805 nm and 840 nm was observed with controlled peak separation around two nanometers, which corresponds to approximately one terahertz. Dual wavelength laser operation is possible using a novel intracavity two plate birefringent filtering element.